Los “otros” mexicanos. La visión de los intelectuales decimonónicos de los afrodescendientes (Tzintzun, Revista de Estudios Históricos, 2016)
This article presents the different visions of famous Nineteenth century intellectuals such as Fray Servando Teresa de Mier, Lorenzo Zavala, Lucas Alamán and José Luis Ma. Mora about the African Descent people. The main contribution of this work lies on recovering multiple views about this population from the more relevant thinkers of the first half of the nineteenth century that will leave a mark in politics and historiography of the following decades about the population of African origin. It is concluded that the concern of these writers for creating a modern, homogeneous nation, facing a reality with an extended ethnic, linguistic and cultural diversity with the knowledge and reproduction of certain racial prejudices developed in taxonomic works influenced in the silencing of the African descent people presence in the national history
Keywords: african descent people; intelectuals; xix century; historical narrative